FAKTOR-FAKTOR DETERMINAN PINJAMAN : STUDI PADA KOPERASI SHT - Kurniawati, Deti; Suprayogi, Toteng Temy; Mugeno, Mugeno (Economic Faculty, Attahiriyah Islamic University, 2017)
This study aims to examine the determinant of loans based on the member characteristics. A total of 50 members made participants using purposive. Analysis techniques using non-parametric approach, cross-tabulation and chi-square test. The results of the analysis concluded that: (1) the length time as member is not related to the amount of the loan; (2) there was no difference in income levels of respondents with an average loan; (3) the use of the proceeds of the loan has no relationship with income level; (4) long been a member of a cooperative relationship with the magnitude of the average of loans. Keywrods: financial loan, koperasi